Common Linguistic Errors among Education College Students at Al-Furat University (Journal of Hama University, 2025)
The research aimed to identify written linguistic errors (spelling and grammatical) among students of the College of Education at Al-Furat University. To achieve the research objective; The researcher adopted the descriptive analytical method, The researcher compiled a list of linguistic errors (spelling and grammatical) consisting of (71) linguistic errors, including (29) grammatical errors, and (42) spelling errors. With this list, the researcher analyzed (150) exam papers for fourth-year students at the College of Education in Deir ez-Zor and Raqqa who took the practical exam for the Arabic language subject in the year 2022-2023. The results of the analysis showed that the linguistic errors, which were common at a rate of (25%), were (17) grammatical errors and (24) spelling errors. It also appears that the most frequent grammatical errors among students are: The sub-grammatical mark does not fit the grammatical position of the noun at a rate of (98.67%). The most frequent spelling errors among students are: Do not write the stress or add it in a wrong place (100%).Also, the percentage of spelling errors among College of Education students is (66%), which is more common than grammatical errors, which amounted to (34%) of the total linguistic errors.The results also showed that there were no differences in the degree of prevalence of linguistic errors among students of the College of Education depending on the college.
Keywords: common linguistic errors, students of the College of Education, content analysis.